2017
DOI: 10.1021/acs.biochem.7b00613
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Mediated Quinary Interactions Modulate In-Cell Protein Activities

Abstract: Ribosomes are present inside bacterial cells at micromolar concentrations and occupy up to 20% of the cell volume. Under these conditions, even weak quinary interactions between ribosomes and cytosolic proteins can affect protein activity. By using in-cell and in vitro NMR spectroscopy, and biophysical techniques, we show that the enzymes, adenylate kinase and dihydrofolate reductase, and the respective coenzymes, ATP and NADPH, bind to ribosomes with micromolar affinity, and that this interaction suppresses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(95 citation statements)
references
References 79 publications
(185 reference statements)
7
88
0
Order By: Relevance
“…In vitro kinetic assays performed in the absence and presence of ribosomes and found that the ribosome acted as an uncompetitive inhibitor of ADK activity ( Figure 7A). Similar experiments performed using [U-2 D, 15 N] dihydrofolate reductase, DHFR, showed that DHFR engages in micromolar binding affinity quinary interactions with ribosomes, and that its coenzyme, NADPH, binds to ribosomes with a K d of ∼4.5 μM [10]. The results showed that the ribosome acts as a competitive inhibitor of DHFR activity ( Figure 7B).…”
Section: Functional Interactionssupporting
confidence: 65%
See 1 more Smart Citation
“…In vitro kinetic assays performed in the absence and presence of ribosomes and found that the ribosome acted as an uncompetitive inhibitor of ADK activity ( Figure 7A). Similar experiments performed using [U-2 D, 15 N] dihydrofolate reductase, DHFR, showed that DHFR engages in micromolar binding affinity quinary interactions with ribosomes, and that its coenzyme, NADPH, binds to ribosomes with a K d of ∼4.5 μM [10]. The results showed that the ribosome acts as a competitive inhibitor of DHFR activity ( Figure 7B).…”
Section: Functional Interactionssupporting
confidence: 65%
“…Excluded volume effects and molecular crowding increase the effective concentrations of cytosolic species, virtually assuring the likelihood of transient low-affinity interactions. In-cell NMR spectroscopy [7] has proven to be a reliable technique to identify protein interaction surfaces under these conditions [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in‐cell NMR has emerged as a powerful technique for identifying sticking inside cells. In particular, these experiments have highlighted the importance of surface interactions in regulating non‐specific sticking of macromolecules, which can destabilize proteins, and suppress or activate enzymes . In vitro experiments in dilute cell lysates have had limited success replicating non‐steric interactions identified by in‐cell NMR …”
Section: Figurementioning
confidence: 99%
“…Non‐steric interactions refer to all interactions between the protein and its environment aside from volume‐excluding steric interactions, encompassing nonspecific sticking between macromolecules and weak quinary interactions evolved for function . The surface of proteins is particularly important in determining the strength of non‐steric interactions, which can stabilize or destabilize proteins and suppress or activate enzymes . To mimic non‐steric interactions in vitro, dilute cell lysate or lysis buffer can be added to the buffer .…”
Section: Introductionmentioning
confidence: 99%